(untitled) (Archives of Criminology, 1972)
The study presents the findings of an inquiry conducted among 60 young adults (male) serving sentences for robbery in a Warsaw prison. These 60 offenders (aged I7 - 20) formed part of a total of 229 young adults convicted of robbery and confined in this Warsaw prison between 1 October, 1966 and 30 November, 1968, with regard to whom details were secured of their criminal records from the age of ten. Of these 229 young persons, whose average age was 18.8, as many as 76 per cent had previous convictions, 58 per cent of them having appeared in juvenile courts and 48 per cent in criminal courts for offenders over 17 years of age. Of those who had appeared in juvenile courts 42 per cent had three or more appearances. The fact that three-quarters of the young adults convicted of robbery in Warsaw are repeated offenders indicates a need to analyze the types of their offences. As regards offences committed as juveniles, these were usually thefts, the proportion of crimes of violence not exceeding 18 per cent. Above the age of seventeen, however, the structure of their offences changes, since 36 per cent involved acts of physical assault and 14 per cent offences with verbal aggression (i.e. slander); offences against property, on the other hand, came to 48 per cent. The young recidivists convicted of robbery differ basically (p < 0.001) from young adults guilty of other offences (previously surveyed by the Department of Criminology) since the majority of the latter (as much as 67 per cent) were offences against property (usually larceny). The above evidence indicates therefore that the problem of aggressiveness requires special attention in studies of robbery offences committed by young adults. A more detailed inquiry was, as has been said, conducted among 60 young adults serving sentences for robbery, of whom 82 per cent had more than one previous conviction. The control group consisted of 43 young recidivists convicted of various offences (chiefly theft) with the exception of robbery. The first point to be made is that the subjects revealed, according to the accounts of their mothers, marked behaviour disorders as early as pre-school age (overactivity and restlessness, stubbornness, etc.). Evidence of such behaviour disorders below the age of seven was found much more frequently among offenders convicted of robbery (61 per cent) than in the control group containing young adult recidivists who had committed other offences (34 per cent). Only 69 per cent of the robbery offenders had completed the seven grades of elementary school, and of these only 12 pet cent had never been kept back a grade, while 24 per cent had fallen back one grade, 39 per cent two grades and 24 per cent three or more grades. This poor progress at school cannot be explained by lower levers of intelligence since 68 per cent of the subjects had normal IQs, 24.5 per cent were dull, 6.2 per cent were on the borderline of mental deficiency and 2 per cent were morons. Among the young robbery offenders (and the young recidivists as well for that matter) there had been frequent cases of truancy (77 per cent) and this had begun at an early age since almost half had got into the habit before the fourth grade. Thefts had been committed by 61 per cent of the subjects below the age of 15. The majority (65 per cent) had no vocational qualifications. Altogether among all the young adult robbery offenders with previous convictions, 16 per, cent had never been gainfully employed, and 49 per cent had jobs for less than half the period they were at liberty after completing their sixteenth year. At the time the robbery was committed, the percentage in employment did not exceed 17 per cent. The subjects spent their time among demoralized peers with whom they drank. The nature of the environment in which they mixed can best be seen from the fact that among the persons who were accomplices to their robberies (almost always young adults or juveniles), as many as 75 per cent had been previously convicted and 60 per cent frequently drank to excess. It should be noted that the young recidivists in the control group convicted of other offences and drawn from persons with a record of theft as juveniles, had made even poorer progress at school than the robbery offenders, had in fewer cases completed elementary school, had more frequently run away from home, had started to steal regularly at an earlier age and had committed many more thefts as juveniles and children. The inquiry found, however, that the robbery offenders had displayed personality disorders at an earlier age and had started to drink younger and done much more drinking at 16 – 17 years of age. The data on the drinking habits of the robbery offenders merit special attention. It was found that only 23 per cent of these young adults drank less frequently than once a week, 55 per cent drank 2-3 times a week, and 22 per cent drank at least four times a week (these figures are certainly not an accurate reflection of the degree of drinking which was undoubtedly even higher). It should be emphasized that 43 per cent of the subjects began to drink wine or spirits at least once a week below the age of 16, and 75 per cent were drinking with the same regularity before their 17th birthday. In the period preceding the robbery a large percentage of the young adults (52 per cent) were drinking large quantities of alcohol at each session (at least 1/4 litre in terms of spirits) 2 - 3 times a week or more. They drank wine or vodka, or both. It should not be forgotten in considering these figures that some 60 per cent of the robbery offenders were only 17-18 years of age. Furthermore 42 per cent of the 17-18 age group had been drinking 2-3 times a week or more for at least two years, and 50 per cent of the 19 -20 age bracket had been doing so for at least three years. A third of the subjects admitted to intoxication at least once or twice a month, and a half recorded that they were inebriated several times a month. A very large majority (c. 80 per cent) were under the influence of alcohol when they committed their robbery. In the psychological inquiries detailed attention was given to the problems of aggression in the case of the young robbery offenders, their level of aggressiveness being determined from the evidence of aggressive behaviour in childhood and later yielded by interviews with both the subjects themselves and their mothers. Ratings of “very aggressive” were scored by 62 per cent of the young robbery offenders. In comparison with the findings of the Department of Criminology study of other samples of juvenile and adult recidivists (not convicted of robbery), it has been found that the robbery offenders do indeed display a greater incidence of aggressive behaviour and score higher in the Buss-Durkee aggression questionnaire. The robbery offenders not qualified as “very aggressive”, (38 per cent) also had occasional acts of aggression in their past career, and 25 per cent of them had even been previously prosecuted for offences containing an element of violence. However, they differed in certain respects from the robbery offenders qualified as “very aggressive”. Among the latter regular drinking was more frequent (p < 0.001) and had begun at an earlier age (p < 0.01), thefts had been more common and the rate of recidivism was greater. Evidence of the presence of such characteristics as overactivity, impulsiveness, etc., in childhood was also more frequent (p < 0.05). In addition they possessed a higher rate of brain damage. Very aggressive robbery offenders more frequently displayed overactivity whereas the non-aggressive offenders tended to have clearly passive personalities (p < 0.02) inclined to let others take the lead. Attention should finally be drawn to the more frequent occurence among the “very aggressive” offenders (in comparison with the remaining young adults convicted of robbery) of certain adverse conditions in their home background. There were many more cases of among these subjects of defective emotional relationships between parents and son (p < 0.01) and more frequent employment of brutal corporal punishment (p < 0.02). These are factors found by various inquiries to be conducive to the development of aggressive attitudes. However, as regards such environmental factors as alcoholic or criminal parents and siblings, no significant differences were found between the backgrounds of the aggressive and non-aggressive robbery offenders. In analysing the problem of aggressiveness the question of brain damage should not be overlooked. In the case of as many as 29 of the sample (49 per cent) there was evidence pointing to such a condition with a high degree of probability. These subjects displayed, it was found, more frequent symptoms of behaviour disorders and social maladjustment such as frequent stealing (p < 0.001), early excessive drinking (p < 0.02), considerable violence (p < 0.001) and more frequent self-aggression (p < 0.02). This multiplication of behaviour disorders among offenders suffering from brain damage points to greater adaptation difficulties further compounded by their home circumstances. Among the whole sample of young robbery offenders there were only 16 per cent who were not found to be subject either to brain damage or decidedly adverse influences at home. The homes of the young robbery offenders present as negative a picture as those of the previously studied recidivists convicted of other offences. Only 57 per cent of the former spent their childhood in unbroken homes. As many as 65 per cent of their fathers regularly drank to excess, and at least 27 per cent of them can be qualified as alcoholics. The percentage of fathers with a criminal record was less than 23 per cent and the majority of these were not persistent offenders. Most of their offences were of a drunk-and-disorderly nature. The subjects’ fathers were by and large persons with a low standard of education and vocational qualifications: only 28 per cent had advanced beyond elementary school, usually to vocational school. Almost all the subjects came from the homes of unskilled or low-skilled labourers. Only a third of their homes were relatively well off. Among a large majority of the fathers (71 per cent) and as much as 45 per cent of the mothers there was evidence of their emotional relationship with their children being inadequate. In the case of 61 per cent of the fathers there was very frequent employment of excessively severe corporal punishment of the subjects. The inquiry also revealed the typical fact that 51 per cent of the brothers of the young adults serving sentences for robbery had (by the time they had completed their tenth birthday) been before the courts and that the same percentage were heavy drinkers. Only in 28 per cent of the homes was there no evidence of frequent excessive drinking and criminal offences by brothers. A comparison of the home environments of the young recidivists convicted of robbery and those convicted of other offences revealed no differences as regards such factors as family structure or alcoholic and criminal parents and siblings (except that the brothers of the robbery offenders had committed more offences of an aggressive nature than the brothers of the persons in the control group). However, marked differences were found in the emotional relationship of parents to children and the practice of severe corporal punishment which was much more frequent in the case of the fathers of the robbery offenders. These are factors which various inquiries have found to be conducive to the formation of aggressive attitudes.